Proposed Strategy Formulation and Implementation for Puri Luluran Wanoja - Ratnapuri, Chyntia Ika; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract. Nowadays, along with the increasing density of population growth and activity in Indonesia especially in Bandung as one of the biggest city in Indonesia, clearly give significant impact against any person. High levels of stress due to the density of activity became a common thing nowadays, especially for a woman. For the reasons above, the importance of taking the time to take care the body at the spa became very important needs in the present era. The development of a spa industry nowadays was growing rapidly and the competition was very intense. This issue gives a fairly significant impact on the company's condition such as the hijacking of the therapists, declining in profit margin, declining in number of customers, the determination of the price more stringent. Therefore, Puri Luluran Wanoja needs to formulate and implement strategies to compete in the industry and gain a competitive advantage.After identifying the business issue, the next step is to make an analysis to determine the companyâ€™s current condition by scanning the companyâ€™s environment that was divided into external and internal analysis. This analysis used to determine the strength, weaknesses, opportunities, and threats of the company to compete the tight competition in spa industry. The result of this external and internal analysis will be used to find the root cause of the problem and strategy formulation can be made based on the root of the problems occurred. This strategy formulation required to anticipate the high level of competition and then implementing these strategies to solving the problems.The internal and external analysis also used to determine the companyâ€™s position in industry by performing IFAS and EFAS calculations. According to IFAS and EFAS score, Puri Luluran Wanoja is in Growth Position of corporate strategy but still lack of differentiation that can be the competitive advantages in the face of fierce competition in the spa industry. Puri Luluran Wanoja still requires uniqueness and diversification, especially in service to be offered to customers so that can built the customers loyalty. Therefore the suitable diversification strategy is Concentric (Related) Diversification strategy. For business strategy, Puri Luluran Wanoja chooses to conduct a differentiation strategy in order to gain competitive advantage. Some strategy differentiation that will be done by Puri Luluran Wanoja in the future is â€œOne Stop Healing Placeâ€, the unique service of treatment, and built children playground.Strategies should be implemented through an action plan based on strategy formulation of Puri Luluran Wanoja which are make an massive advertisement strategy, using computerize system, create a unique treatment, provide new facilities and create â€œone stop healing placeâ€. The Milestone, Action Plan and Recommendation expected to increase profits and gain competitive advantages to compete in this tight competition of spa industry.Key Words: PURI LULURAN WANOJA, competitive advantages, strategy formulation